Dukungan Keluarga Dengan Kepatuhan Minum Obat Pada Pasien Skizofrenia Di Puskesmas Kota X - Rahayu , Purwanti Endah; Kurniawan , Harri; Syntia , Soneta (CV. ITTC INDONESIA, 2024)
This study aims to determine the relationship between family support and medication adherence to schizophrenia patients at Public Health Center, City X. The independent variable in this study is family support and the dependent variable is medication adherence. Measuring instruments used in this study were the family support scale and medication adherence scale. The sample selection technique in this study was purposive sampling technique. The sample in this study were 95 schizophrenic patients at Public Health Center. Validity and reliability tests in this study used the Alpha Cronbach technique. The results of the validity coefficient on the family support scale ranged from 0.360 to 0.727. The results of the validity coefficient on the medication adherence scale ranged from 0.309 to 0.682. With the reliability coefficient of family support of 0.898 and the scale of adherence to taking medication of 0.849. Based on data analysis, the correlation value between family support and medication adherence was obtained by r = 0.564 with a significant level of p = 0.000, which means that the hypothesis is accepted. It shows a moderate level and positive direction, meaning that the better family support, the higher the adherence to taking medication, and conversely the less good family support, the lower the compliance with drinking. This shows that there is a significant relationship between family support and medication adherence in schizophrenic patients at Public Health Center X